Desempenho do melão fertirrigado com controle da concentração do nitrogênio e do potássio na água de irrigação - Oliveira Filho, José Nilson (2019)
Against of the economic importance of melon crop in the West region of the state of Rio Grande do Norte, Brazil and the need to develop technologies that help in the production process of this crop, in order to maintain productivity and quality with the optimization of the required inputs, was aim in this research, to produce fertirrigated melon in the Brazilian semi-arid conditions, being the culture submitted to nitrogen and potassium levels and evaluated its concentrations throughout the cycle, by monitoring the soil solution and verifying the interference of the fertilization input in the foliar tissue of the melon crop, in the yield and quality of the fruits and in the fertility of the soil. Thus, the experiment was conducted on a farm in the municipality of Upanema, under a randomized block design, with five treatments and six replicates. The treatments were the combinations of nitrogen and potassium applied by fertigation. The soil solution evaluation was based on the installation of porous capsule extractors in plots of all treatments, where samples were collected twice a week during the cycle, when fertigations were performed. The analysis of the melon leaf was carried out from the collection of the diagnostic leaf of the melon for all the treatments. Yield and quality were evaluated at harvest time by counting all fruits, separation in class and weighing. Fruits were harvested ripe and green where the form factor, pH, titratable acidity, soluble solids content, maturation index and fruit firmness were analyzed. The soil analysis at the end of the experiment was based on the composite samples end were analyzed the pH, the electrical conductivity of the saturation extract (CEes), phosphorus, potassium, sodium, calcium and magnesium exchangeable, nitrogen, potassium, calcium and sodium in the saturation paste extract. Thus, there were variations along the cycle in the concentrations of the nutrients studied in the soil solution. In the leaf tissue, no differences were observed between the treatments for nitrogen, and for the potassium, the T4 treatment (150 mg L-1 of K) was the one that provided the greatest increase. Regarding the productivity of the melon, no differences between treatments were observed. For the qualitative parameters of the melon, in general the fertilizations did not have great influence on the quality of the fruits. In the soil, it was observed that nutrient sources contributed to nutrient concentration increases being the pH, CEes, exchangeable potassium, the nitrogen, the calcium and the potassium of the saturation extract differed statistically among the treatments applied